2004
DOI: 10.4161/cc.3.6.927
|View full text |Cite
|
Sign up to set email alerts
|

Histone-Deacetylase Inhibitors for the Treatment of Cancer

Abstract: Histone deacetylase inhibitors (HDACi) are a promising new class of chemotherapeutic drug currently in early phase clinical trials. A large number of structurally diverse HDACi have been purified or synthesised that mostly inhibit the activity of all eleven class I and II HDACs. While these agents demonstrate many features required for anti-cancer activity such as low toxicity against normal cells and an ability to inhibit tumor cell growth and survival at nanomolar concentrations, their mechanisms of action a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 106 publications
1
122
0
2
Order By: Relevance
“…Previously, studies have reported that HDACIs generally induce a G1 phase arrest at lower concentrations and a G2/M phase arrest at higher concentrations Lindemann et al, 2004). We confirmed that the cells were indeed not arrested in G1 by looking at cyclin D1 mRNA levels by RT -PCR, a marker for G1 phase arrest.…”
Section: Effects Of Vn/66-1 and Ms-275 On Cell Cycle And Proliferationsupporting
confidence: 85%
See 1 more Smart Citation
“…Previously, studies have reported that HDACIs generally induce a G1 phase arrest at lower concentrations and a G2/M phase arrest at higher concentrations Lindemann et al, 2004). We confirmed that the cells were indeed not arrested in G1 by looking at cyclin D1 mRNA levels by RT -PCR, a marker for G1 phase arrest.…”
Section: Effects Of Vn/66-1 and Ms-275 On Cell Cycle And Proliferationsupporting
confidence: 85%
“…Since PCa is one of the leading causes of deaths worldwide, there is an urgent need to identify effective agents against this disease. Retinoids, rexinoids, retinoid-related molecules (RRMs) and histone deacetylase inhibitors (HDACIs) have shown promising biological activities as single agents in several preclinical studies of both haematological and solid malignancies (Altucci and Gronemeyer, 2001;Lindemann et al, 2004;Bolden et al, 2006;Njar et al, 2006a). Because of the heterogeneous nature of PCa, we hypothesise that agents/ combination of agents affecting various pathways involved in PCa growth and survival may be advantageous.…”
mentioning
confidence: 99%
“…Unlike the alterations in HDACs associated with neoplasms, structural alterations in HATs, including translocations, amplifications, deletions and point mutations have been found in various human cancers-both hematological and epithelial [Lehrmann et al, 2002;Rosato and Grant, 2003;Lindemann et al, 2004;Marks et al, 2004;Drummond et al, 2005]. For example, the HATs, CBP and p300, are altered in some tumors by mutation or translocation.…”
Section: Histone Deacetylases (Hdacs) and Histone Acetyltransferases mentioning
confidence: 99%
“…SAHA, LAQ824, LBH589A, and PXD-101 are hydroxamate HDAC inhibitors that have moved forward in clinical trials [Lindemann et al, 2004;Marks et al, 2004;Rosato and Grant, 2004;Piekarz et al, 2004b;Drummond et al, 2005;]. An oral preparation of SAHA is phase I and phase II clinical trials [Kelly et al, In Press].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…HDACi, as a new class of chemotherapeutic agents, show significant pro mise against a variety of cancers in clinical trials [9]. Most available HDACi inhibit all class I and II HDACs, thereby increasing acetylation of histone and nonhistone protein targets [10]. In vivo, histone acetylation depends on the balance between histone acetyltransferase (HAT) and histone deacetylase (HDAC), which has been proposed to play an important role in transcriptional regulation by altering chromatin structure [11].…”
Section: Introductionmentioning
confidence: 99%